Pengaruh Kecerdasan Emosional dan Spritual Terhadap Sikap Etis Pekerja Pada PT Asuransi Umum Bumiputera Muda 1967 - widayat, prama (Komunitas Manajemen Kompetitif, 2016)
Abstract: The objective of the research to know and explain the correlation of influencing variables of emotional quotients, spiritual quotients on employees ethical attitudes. The method used in this study is to survey approach of 100 employees at PT Asuransi Umum Bumiputera Muda 1967 at Head Office, Kebayoran and Jakarta khusus. The Technique of sampling used in this research is done by area sampling. The result of the research showed that the variables of emotional quotients, spiritual quotients on employees ethical attitudes. Emotional quotients and spiritual quotients altogether simultaneously influence employees ethical attitudes, while the rest was influence by the other variables which did not to be explain in the research. Keywords: Emotional Quetion, Spritual Quetion and ethical attitudes